1996
DOI: 10.1002/(sici)1098-2752(1996)17:5<264::aid-micr5>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Functional results of 46 thumb replantations and revascularisations

Abstract: The functional results of 46 patients with isolated thumb replantations and revascularisations were evaluated in the outpatient clinic. The modified system for evaluation of reattached parts proposed by Burton was used. The system for functional evaluation of hands consisted of three major fields: socioeconomic factors, objective assessment and subjective assessment. Certain potential factors which might have influenced the functional results were analysed using Kruskal-Wallis's and Wilcoxon's sum of ranks tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 9 publications
1
10
1
2
Order By: Relevance
“…12 These results are consistent with those of Janezic et al in nonisolated thumb amputations, which showed that functional outcome is lower in crush and avulsion injuries. 15 However, even skill saw amputations, which are often classified as sharp injuries, may be associated with severe local damage, which differentiates them from other guillotine injuries. 1,16 Our analysis includes these skill saw amputations as sharp injuries, although one could argue for the classification in the crush category.…”
Section: Pinch and Grip Strengthsupporting
confidence: 54%
See 1 more Smart Citation
“…12 These results are consistent with those of Janezic et al in nonisolated thumb amputations, which showed that functional outcome is lower in crush and avulsion injuries. 15 However, even skill saw amputations, which are often classified as sharp injuries, may be associated with severe local damage, which differentiates them from other guillotine injuries. 1,16 Our analysis includes these skill saw amputations as sharp injuries, although one could argue for the classification in the crush category.…”
Section: Pinch and Grip Strengthsupporting
confidence: 54%
“…Using Burton's system for the evaluation of reattached parts, Janezic et al found that for nonisolated thumb amputations, the best functional outcomes were obtained distal to or including the IP joint, with worse outcomes associated with replants at the level of the carpometacarpal joint or metacarpal. 15 Our data in isolated thumb amputations suggest a similar trend with decreased pinch and grip strengths with more proximal injuries; in fact, we describe a statistically significant difference when comparing the grip strengths of zone I injuries with zone II and III injuries. Other studies do not report on the correlation between zone of injury and mean pinch and grip strengths after replantation of the isolated, amputated thumb.…”
Section: Pinch and Grip Strengthmentioning
confidence: 99%
“…1,2 Since that time, thousands of replant procedures have been performed, and the practice has become so ingrained in popular culture that severed body parts of any size or condition nearly always accompany the injured patient to the hospital in the hope that they can be replanted. 3,4 Replantation is complicated and costly. It requires prolonged operative time, long recovery periods, multiple procedures, and motivated patients to achieve optimal outcome.…”
mentioning
confidence: 99%
“…La distraction du cal permet d'améliorer la fonction dans les cas de doigt court sans sacrifice de doigt ou d'orteil et les risques inhérents à tout geste microchirurgical [15]. De plus, la sensibilité distale est toujours conservée après distraction [16].…”
Section: Discussionunclassified